Synthesis of carbon nanotubes on surface of recovered carbon fibers by chemical vapor deposition, as a sizing process to obtain a hybrid material - García Montes, Saida Mayela (2017)
Carbon fibers recovered from composite materials in structural components reaching end-of-life can be treated with the synthesis of carbon nanotubes (CNTs) directly grown on the carbon fibers (CFs) surface to produce reinforcements which can be used in new high-performance composite materials. The development of high performance materials with improved properties by anchorage and growth of Carbon Nanotubes on Carbon Fibers surface is increasing the interest of industry and related technology departments. CNTs attached to CFs surface are interesting candidates for novel composite materials with exceptional mechanical, thermal and electrical properties. Synthesis of carbon nanotubes using catalytic Chemical Vapor Deposition (CVD) method is an increasing area of academic research which is also attracting industrial attention due to the relatively low synthesis temperatures ranging from 500°C to 1100°C which can be easily scaled-up for industrialization. In this research, the CVD method was used and studied for the synthesis and growth of CNTs on CFs influenced by the concentration of Nickel (Ni) nanoparticles as a catalyst. The CNTs were synthesized by decomposing Ethanol and Isopropanol as a carbon source, which at the same time worked as a solvent, in an Argon (Ar) atmosphere. Moreover, Ni(NO3)2 * 6H2O was used as precursor of Ni nanoparticles. Ni concentration experimentally controlled between 0 – 5.96 wt %. The CFs were recovered from an epoxycarbon fiber composite reaching end-of-life by a thermal recycling process of pyrolysis at a temperature of 480°C for 30 min. Before the CNTs synthesis, the CFs were analyzed by Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) to identify elements present on CF surface. The EDS results showed that the original sizing on CFs surface was removed. All samples were characterized by different techniques such as Scanning Electron Microscopy (SEM) for morphology, Raman Spectroscopy for structural characterization and Pseudo-Mechanical testing to evaluate the CNTs anchorage to the CF surface.